REVISITING THE IMPLEMENTATION OF TASK-BASED LANGUAGE TEACHING (TBLT) IN INDONESIAN SECONDARY SCHOOL: CURRENT ISSUES AND POSSIBILITIES - Ismail, Mohamad Arif (PEOPLE: International Journal of Social Sciences, 2017)
Task-Based Language Teaching (TBLT) has been widely administered in Asian countries including Indonesia. This paper aims to investigate its implementation in Indonesian secondary school context using the previous research to present comparison. As identified, either target language issue and national examination as it is applied in the curriculum remain in the same situation. Another finding has indicated that the notion of TBLT contradicts to the cultural value of Indonesian students. Having reviewed the relevant studies, this article suggests some potential alternatives in order to move forward: 1) utilizing the teaching procedure called ‘Engage, Study, Activate’ (ESA), 2) employing ‘mediated learning’ and 3) embedding local culture in the teaching materials. Finally, this study addresses the possibility of TBLT in the future particularly in Indonesian context.